Kajian Penanggulangan Gizi Buruk di Kalimantan Selatan - Maliani; Latifa Suhada Nisa; Dewi Siska; Sajiman (Jurnal Kebijakan Pembangunan, 2021)
Toddlers in Indonesia experience a double burden problem, some children are obese but others experience stunting, emaciation, and malnutrition. Nutritional problems if not addressed will cause the Indonesian nation can experience a lost generation. The occurrence of malnutrition can be prevented if the root cause of the problem in the community concerned can be known, so that overcoming the problem of nutrition can be done more fundamentally through handling the root of the problem. The purpose of this study is to identify the causes of malnutrition, identify the implementation of efforts to overcome malnutrition, and formulate strategies to overcome malnutrition in South Kalimantan. This research is a descriptive study with a combination method combining qualitative and quantitative approaches. The results showed the number of malnutrition in South Kalimantan that was found in 2018 to September was 95 cases. Cases of malnutrition were found mostly with non-clinical symptoms. Most cases of malnutrition found with clinical symptoms are marasmus. Most of the cases in 2018 were caused by poverty + poor parenting + lack of sanitation. Efforts to combat malnutrition in South Kalimantan are not only carried out by the health department but also supported by cross-sectors which are included in sensitive interventions, including social services through PKH programs and non-cash direct assistance (literature, basic food distribution, business capital assistance, home rehabilitation) not living) and also the food security department through KRPL and CPP programs, and others. However, coordination between related agencies in managing malnutrition problems, especially at the district / city level, is still not optimal. High commitment from regional leaders is needed for the integration of all related sectors.